2014
DOI: 10.1111/jicd.12116
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of five radiographic dental‐age estimation methods in a population of Malaysian children

Abstract: The Cameriere method of dental-age estimation is highly valid and reliable for Malaysian population, followed by the Willems and Nolla methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 20 publications
6
52
0
9
Order By: Relevance
“…Considering heterogeneous nature of different population groups included in this systematic review, the 'random effects model' of meta-analysis was applied. As presented in Figure 2, statistically significant overestimation was reported for Malaysian and Indian subjects studied by Kumaresan et al 14 Overall, meta-analysis showed a substantial difference between the chronological age (CA) and the dental age (DA) (WMD = 0.35, 95%CI = 0.07, 0.63, P = 0.0005) of individuals of almost all studies considered in this meta-analysis and explained in Figure 2.…”
Section: Quantitative Analysismentioning
confidence: 53%
See 3 more Smart Citations
“…Considering heterogeneous nature of different population groups included in this systematic review, the 'random effects model' of meta-analysis was applied. As presented in Figure 2, statistically significant overestimation was reported for Malaysian and Indian subjects studied by Kumaresan et al 14 Overall, meta-analysis showed a substantial difference between the chronological age (CA) and the dental age (DA) (WMD = 0.35, 95%CI = 0.07, 0.63, P = 0.0005) of individuals of almost all studies considered in this meta-analysis and explained in Figure 2.…”
Section: Quantitative Analysismentioning
confidence: 53%
“…Nolla's technique 4 of dental age assessment calculates the mineralization status of permanent teeth through standard ten stages and, it is a universally accepted system for calculating dental ages of wider ranges. It utilizes developmental stages of teeth for age assessment, which was initially applied to a published studies [6][7][8][9][10][11][12][13][14][15][16][17] were included in this systematic review. A quantitative metaanalysis was also conducted based on 10 studies 6-7, 10-17 for expressing the mean estimates (overestimation or underestimation) and the standard deviation of their estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A forma subjetiva pode ser definida como aquelas presentes nos estudos precursores de diversas técnicas que tiveram início na década de 60 e 70, como os O método de Haavikko já é um método bastante estudado 14,[18][19][20]36,37,46,51,54,60,65,69 18,20,54,64,69 . Logo em seguida, é possível abranger os estudos nos quais o sexo (masculino e feminino) foram analisados separadamente 14,[18][19][20]33,36,37,41,46,51,54,64,69 . Por último, é muito comum encontrar estudos 14,18,19,41,64 , que além de analisarem os sexos separadamente, criam subgrupos dentro de cada sexo de acordo com um intervalo de idade pré-determinado.…”
Section: Discussionunclassified